DESIGN OF A HIGH-SENSITIVITY DEVICE FOR DETECTING WEAK MAGNETIC FIELDS - Trong Vinh Dao; Dang Khanh Le; Minh Huy Le; Dang Khoa Nguyen; Van Su Luong (Tạp chí Khoa học Đại học Đà Lạt)
An anti-serial fluxgate sensor configuration is proposed in this report. The design comprises two identical bilayer-rod fluxgate sensors connected anti-serially in a straight line. Each bilayer-rod sensor is constructed of an excitation coil and a pick-up coil wrapped around a core. The core material consists of Metglas ribbon, an amorphous alloy with high permeability, negligible hysteresis, and a high saturated magnetic field. The core is cut into a bar shape and uses double layers to enhance modulated flux density. A high sensitivity of 10 mV/Oe (with excitation of 45 kHz and 250 mA) is obtained experimentally with low noise of 1´10-5 Oe/Ö Hz at 1 Hz. In measurements of weak magnetic fields, the azimuth response indicates its vector feature. The proposed design is suitable for electronic compass and displacement applications.